Knowledge Sharing for Creating School Intellectual Capital. (2nd June 2015) - Cheng, Eric C.K.
Abstract: This study attempts to verify whether knowledge sharing would create school intellectual capital (IC). It conceptualizes school IC as human, internal and external capital which is supposed to be enhanced by knowledge sharing among teachers. A cross-sectional quantitative survey was applied to analyze knowledge sharing that would enhance the school IC, with a structural equation model applied. Results confirmed that knowledge sharing is the predictors of all three components of school IC including internal, external and human capital. This study draws the conclusion that the concept of IC could be applied in school organization and strengthened by creating effective organizational communication strategies. School leaders could cultivate communities of practice in their schools to facilitate knowledge transfer for building school IC.